AGRIBISNIS SAYURAN ORGANIK PADA KELOMPOK WANITA TANI VIGUR ORGANIK KEDUNG KANDANG KOTA MALANG - Peni Peni; Asnah Asnah; Farah Mutiara (BUANA SAINS, 2022)
The general problem of organic vegetable farming is the cultivation technique which must have organic principles, both in the use of inputs and cultivation techniques. In addition, the market for organic products is still limited. This study aimed to formulate the best strategy for the Vigur Organic Women's Farmer Group. The research location was determined used purposively and the sample was taken by accidental sampling. The data was analyzed by using a qualitative descriptive method using the SWOT analysis method. The results showed that the Vigur Organic Women Farmer Group was in cell IV of the IE matrix, which means that they were carrying out a growth and development strategy, while the results of the SWOT analysis were in quadrant I (growth) with a value of 2.45 in the internal position, namely strength. The priority of the alternative strategy to be developed based on the results of the QSPM (Quantitative Strategic Planning Matric) analysis is to optimize and increase the volume of organic vegetable production with the highest total attractive value (TAS) of 6.44. The priority of the next alternative strategy is to maintain organic certification of 6.12, and the last alternative strategy carried out by the Vigur Organic Women's Farmer Group is to manage and increase cooperation with distributors with a TAS value of 6.00